Genetic signatures of demographic changes in an avian top predator during the last century : Bottlenecks and expansions of the Eurasian eagle owl in the Iberian Peninsula - Gracia, Eva; Ortego, Joaquin; Godoy, Jose Antonio; Perez-Garcia, Juan Manuel; Blanco, Guillermo; Delgado Sanchez, Maria Mar; Penteriani, Vincenzo; Almodovar, Irene; Botella, Francisco; Sanchez-Zapata, Jose Antonio (PLOS ONE, 2016)
Peer reviewed